Konstitusi Hijau: Hak atas Lingkungan Sehat sebagai Bagian dari Hak Asasi dalam UUD 1945 - Muhammad Fadli (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This research is motivated by the urgency of protecting the right to a healthy environment as an integral part of human rights (HAM) guaranteed in the 1945 Constitution. In the context of the Green Constitution, a healthy environment is understood not only as an ecological necessity, but also as a prerequisite for fulfilling the rights to life, health, and well-being. The purpose of this research is to analyze the relationship between environmental rights and human rights, the implications of the green constitution for environmental law and policy, and the challenges of implementing and strengthening environmental protection in Indonesia. The research method used is qualitative with a normative-constitutional approach and descriptive analysis of articles of the 1945 Constitution, Constitutional Court decisions, and national environmental policies. The results of the discussion indicate that the right to a healthy environment has individual, collective, and intergenerational dimensions, so that the state is obliged to guarantee its fulfillment through legal instruments and policies that are ecologically just. The research findings emphasize the gap between constitutional norms and policy practices, weak law enforcement, low public environmental literacy, and the conflict between economic and ecological interests in the era of Society 5.0. The implications of this research are the need to strengthen the role of the Constitutional Court, update regulations based on sustainability, and public participation through digital technology so that the constitutional right to a healthy environment is truly implemented in real terms.